Involvement of retrotransposon L1 in stemness and cellular plasticity. (2nd January 2015) - Apostolou, Panagiotis; Toloudi, Maria; Chatziioannou, Marina; Kourtidou, Eleni; Mimikakou, Georgia; Vlachou, Ioanna; Chlichlia, Aikaterini; Papasotiriou, Ioannis
Abstract: Epithelial-to-mesenchymal transition (EMT) as well as the reverse process, mesenchymal-to-epithelial transition (MET) is important during embryogenesis. EMT is also involved in cancer invasion and metastasis, and can generate cells with properties similar to those of stem cells. Retrotransposons can rearrange the genome by inserting DNA in new loci, thus inducing mutations. This study examines the gene expression of transcription factors involved in EMT and MET. In the second experimental panel, the gene expression of L1 retrotransposon was studied. L1-open reading frame (ORF) 2 mRNA was found to be expressed both in cancer and cancer stem cells, while L1-ORF1 mRNA was expressed only in cancer cells. The suppression of L1-ORF2 gene expression demonstrated that this retrotransposon might affect EMT in colon cancer stem cells. This study highlights that the EMT process seems to differ between cancer cells and cancer stem cells, and that transposable elements seem to be involved in the process, influencing cellular plasticity.